2010
DOI: 10.1002/cncr.25140
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous delivery of the plasma fraction of stored packed erythrocytes promotes pancreatic cancer growth in immunocompetent mice

Abstract: BACKGROUND: Perioperative blood transfusion in pancreatic cancer patients has been linked to decreased survival; however, a causal mechanism has not been determined. During the processing and storage of packed erythrocytes, biologically active molecules accumulated in the acellular plasma fraction; therefore, the authors hypothesized that the plasma fraction of stored packed erythrocytes promoted tumor progression. METHODS: Proliferation and migration of murine pancreatic cancer and control cells were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
1
22
2
Order By: Relevance
“…The results of this study also showed that the CD3 + , CD4 + , CD4 + /CD8 + ratio and NK cells in allogeneic blood transfusion group began to decline immediately after operation and had not recovered on postoperative day 7, indicating that allogeneic blood transfusion can reduce postoperative T lymphocyte subsets and NK cells number of tumor patients thus allogeneic blood transfusion can reduce cellular immune function. By observing impact of allogeneic blood transfusion on immune function in gastric cancer patients, Maeta et al found that allogeneic blood transfusion can significantly reduce the number of NK cells in gastric cancer patients, leading to inhibition of patients' cellular immune function (Barnett et al, 2010). Our study result is basically consistent with the study result of Maeta.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study also showed that the CD3 + , CD4 + , CD4 + /CD8 + ratio and NK cells in allogeneic blood transfusion group began to decline immediately after operation and had not recovered on postoperative day 7, indicating that allogeneic blood transfusion can reduce postoperative T lymphocyte subsets and NK cells number of tumor patients thus allogeneic blood transfusion can reduce cellular immune function. By observing impact of allogeneic blood transfusion on immune function in gastric cancer patients, Maeta et al found that allogeneic blood transfusion can significantly reduce the number of NK cells in gastric cancer patients, leading to inhibition of patients' cellular immune function (Barnett et al, 2010). Our study result is basically consistent with the study result of Maeta.…”
Section: Discussionsupporting
confidence: 90%
“…The model has the advantage of using syngeneic mice and controlling for tumor inoculum (250,000 cells per mouse), transfusion volume (the equivalent of the acellular fraction of pRBCs that a patient would receive with a 2U transfusion, and controlled and relatively minor operative stress. This model revealed marked augmentation of tumor growth and increased lymph node metastasis in vivo compared with animals with tumor, but without transfusion [29]. Interestingly, these results were independent of blood storage time, indicating the presence of bioactive substances that can promote tumor growth may be present in plasma after only 1 d of storage and that lipid mediators may not be causative for pancreas tumor progression in these mice, although mice receiving older blood did develop more ascites.…”
mentioning
confidence: 76%
“…Therefore, preclinical models may offer great opportunities to control for many of these variables and study the effects of transfusion-related immunomodulation (TRIM) on tumor biology in pancreatic adenocarcinoma. Based on the work of Silliman et al [16,17] showing the accumulation of lipid mediators in the acellular fraction of stored pRBCs, the authors have recently demonstrated that this acellular fraction increases tumor cell proliferation and migration in an in vitro model of murine pancreatic adenocarcinoma [29]. These findings led to the intravenous injection of the acellular fraction of pRBCs in immuncompetent mice that previously had been inoculated with Pan02 cancer cells.…”
mentioning
confidence: 99%
“…With this preclinical model, we are able to control for many variables, such as tumor burden and genetic variability that make clinical research difficult (3). Pancreatic adenocarcinoma continues to be a disease of high morbidity and mortality (1,20), with a propensity of metastases, even with small primary tumors (21).…”
Section: Discussionmentioning
confidence: 99%